URBAN/RURAL HYBRIDS: THE URBANISATION OF FORMER SUBURBS (URFSURBS - Kühne, Olaf (Quaestiones Geographicae, 2016)
In pace with changing social developments, cities undergo regular processes of transformation. Thus, following a temporary preference for suburban living, the inner city has for some years now been enjoying a residential renaissance. A further, as yet little noticed, trend is the urbanisation of former suburbs. Encompassing urbanisation and gentrification processes found in the inner-ring suburbs, this entails a breaking of established dichotomies and the development of hybrid phenomena that can be encapsulated in the acronym URFSURBS: ‘urbanisation of former suburbs’. Focusing on examples from Southern California and Greater Paris, this article places these developments in context and outlines their implications for future research.